INSTITUTIONAL ROLE IN PROMOTING PEACEBUILDING AND TACKLING INSURGENCY IN NORTHERN NIGERIA - JIBRIN IBRAHIM GANI; KAMARULZAMAN ASKANDAR (Innovare Journal of Social Sciences, 2025)
The paper aims to provide a solution to tackle insurgency through institutional peacebuilding (PB) in Northern Nigeria. Terrorism in Northern Nigeria has become an issue that has drawn the attention of local and international communities around the globe. The study selected five variables: traditional, religious, educational, non-governmental organizations, and political institutions (PIs) toward PB. The study adopted structural equation modeling using confirmatory factor analysis based on adaptive theory for PB. Three hundred (350) respondents were gathered from different parts of the community, including traditional, religious, educational, and PIs, to justify the model with rigorous analysis. The finding provides insights into institutional activities, their significant role in PB, and how they have improved security challenges in society. A successful concentration on such institutions provides less crime activities within a community and integrates a society locally with its leaders. Further, the institutions should help better decide on security challenges and their respective solution to enhance such institutions and promote PB. This paper justified the key role of institutions in PB and constructed four institutions as new formation variables to tackle insecurity and provide PB